1988
DOI: 10.1038/bjc.1988.35
|View full text |Cite
|
Sign up to set email alerts
|

Local induction of a cytotoxic factor in a murine tumour by systemic administration of an antitumour polysaccharide, MGA

Abstract: When an antitumour mannoglucan prepared from Microellobosporia grisea, MGA was administered i.v. to C3H/He mice bearing the solid MH134 hepatoma, a cytotoxic factor was induced that was detectable in the tumour homogenate by an 8 h cytolysis assay against L-929 fibroblasts. Without MGA treatment, the cytotoxic factor was not detectable in the tumour homogenate. MGA induced the cytotoxic factor in tumour tissue specifically, its level reaching a maximum (24 U ml-1) 3 h after administration of MGA: little if any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 9 publications
0
5
1
Order By: Relevance
“…Otterlei et al (1991) showed that alginate with high M-and MG-blocks (isolated from Ascophyllum nodosum) were much more potent in inducing IL-1, IL-6, and TNF-α cytokine production compared with alginate with high G blocks (prepared from Laminaria digitata) [50]. Mannoglucan showed also TNF-α-like antitumor activity [51]. These results are in contrast with the anti-inflammatory activity of alginate demonstrated in our study.…”
Section: Discussioncontrasting
confidence: 80%
“…Otterlei et al (1991) showed that alginate with high M-and MG-blocks (isolated from Ascophyllum nodosum) were much more potent in inducing IL-1, IL-6, and TNF-α cytokine production compared with alginate with high G blocks (prepared from Laminaria digitata) [50]. Mannoglucan showed also TNF-α-like antitumor activity [51]. These results are in contrast with the anti-inflammatory activity of alginate demonstrated in our study.…”
Section: Discussioncontrasting
confidence: 80%
“…We tested several preparations of AMPH (Sigma Chemical Co.) and AMPH (Fungizone; Bristol-Myers Squibb Co.) with similar results and observed that DMSO neither stimulated the production of TNF nor was a primer for TNF production (data not shown). Additionally, these TNF activities in the supematants of the macrophages stimulated by AMPH preparations and OK432 were immunologically confirmed to be neutralized by a rabbit antibody to TNF prepared as described previously (15). The doubt that the endotoxin that was possibly contaminated in the AMPH preparation might affect TNF production was ex- Endotoxin-insensitive macrophages from C3H/He J mice also produced TNF when stimulated by AMPH and OK432 (data not shown).…”
mentioning
confidence: 71%
“…TNF-␣ induces lysis of malignant cells and causes regression of some animal tumors [52], so that one possible mechanism for the anti-tumoral effect of polysaccharides has been related to induction of TNF [53][54][55][56][57][58]. Now, TNF-␣ production induced by the acidic arabinogalactan ARAGAL (100 mg/kg), following treatment of animals, was increased 26-fold when compared with the control group.…”
Section: Discussionmentioning
confidence: 93%